Improving critical thinking skills in civic education based on project citizen building awareness of environmental issues - Rafzan, Rafzan; Belladonna, Aprillio Poppy; Saputra, Endarman (Universitas Negeri Yogyakarta, 2024)
This research explains how the dimensions of critical thinking develop and are consistent in students by learning directly in a project-based contextual manner through small research that they choose. The research method used is descriptive analysis to analyse the dimensions of students' critical thinking abilities using a quasi-experimental design (a one-group post-test only design). Data was collected by involving active, even semester students taking general compulsory courses in Civic Education, totalling forty students with project model learning. Through small research-based learning or the project citizen model, critical thinking skills will be developed at four levels of critical thinking achievements. Four levels of critical thinking were made into fourteen questions. When the questionnaire has passed the validation process stage, which is prepared using a standard critical thinking ability scheme related to environmental awareness, the questionnaire is also adapted to respondents who have received project citizen model learning. The research findings on students' critical thinking ability towards awareness of environmental issues are included in the high category. Thus, this research shows the success of Civic Education courses in realising a sense of civic responsibility and civic awareness. Then, the results of this research give birth to citizens who can touch on environmental issues; this is the basis for the learning objectives of Civic Education, which is to educate citizens to understand their nation and country.